Aula virtual de Física utilizando Moodle para Primero de Bachillerato de la Unidad Educativa “Provincia de Cotopaxi” periodo 2021-2022 - Alvarez Chiluisa, Francisco José (2022)
In the present research, a virtual classroom is proposed, where the method of Analysis, Design, Development, Implementation and Evaluation was used to create the Physics virtual classroom for the students in the First year of General unified High School at the Educational Unit in Pujilí canton " Cotopaxi Province " period 2021-2022, through the Moodle platform, which was validated by the teachers who teach Physics in the first year of high school, where a checklist was used as an information collection instrument to evaluate the virtual classroom. The research has a quantitative approach, with a propositional level, non-experimental design and cross-sectional type, since the data collection was carried out only once during the research, is based on statistics and the variable is not manipulated. Therefore, we concluded that the virtual classroom is valid for its implementation in this course since it has a validity index of 0.9875. This classroom can enhance student learning skills, as well as have a better sequence of the contents present in Physics within the First year of senior high school. It is recommended, for the creation of a virtual classroom, the educational reality and the needs presented by the students must be analyzed, to focus it on a correct way. Creating a productive online learning environment starts with the right educational tools.